OPTIMIZATION OF PREBIOTICS AND OXYGEN SCAVENGERS FOR MICROCAPSULES OF BIFIDOBACTERIUM BIFIDUM BB01 BY TWO-LEVEL FRACTIONAL FACTORIAL DESIGN - HE CHEN; CHUNXU YAO; YILIN LI; YAJUAN SONG (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
In this paper, protection effects of four oxygen scavengers including sodium erythorbate, ascorbic acid, sodium ascorbate, cysteine hydrochloride and five prebiotics including stachyose, Fructo-oligosaccharide (FOS), Isomalto-oligosaccharide (IOS), Xylo-oligosaccharide (XOS), Galacto-oligosaccharides (GOS) on the microencapsulation of xanthan gum / chitosan Bifidobacterium bifidum BB01 were investigated by single factor experiment and two-level fractional factorial design. The single factor experiment showed that ascorbic acid, sodium erythorbat in oxygen scavengers and XOS, GOS in prebiotics could get higher viable counts and encapsulation yield for preparation of Bifidobacterium bifidum BB01 microcapsules. It also indicated that the variable factors such as sodium erythorbate, XOS and ascorbic acid were significant both for viable counts and encapsulation yield by two-level fractional factorial design. Therefore, these three factors can be further optimized to improve the protection of probiotics by microcapsule technology. So that more probiotics reach the intestines and have a beneficial effect on the human body.